Correlation of platelet cell indices with blood sugar levels in type 2 diabetes mellitus - Dr Dhaval Baraiya; Dr Mahajan SN (Medico Research Chronicles, 2019)
Background: Type 2 Diabetes has been associated with glucose intolerance, hypertension, dyslipidemia, a procoagulant state and an increase in micro and macrovascular disease. Diabetics are at high risk for coronary artery disease. It has been proposed that the complications are a result of chronic hyperglycemia. The increased platelet activity is emphasized to play a role in the development of vascular complications of this metabolic disorder. Platelet volume, a marker of the platelet function and activation, is measured as mean platelet volume (MPV) by hematology analyzers. Diabetic patients have an increased risk of developing micro- and macrovascular disease, and platelets may be involved as a causative agent with respect to altered platelet morphology and function. Aims andObjectives: To assess various platelet indices abnormalities in type 2 DM.Materials and Methods: The present study was a prospective casecontrol type of study that was conducted in Pravara Rural Hospital, Loni. (PRH) with a sample size of 190 (140 cases and 50 controls).Results: The MPV in cases was 10.17 ±1.26 fL and in controls was 10.01 ±1.83fL (P<0.001 'S'). The PDW in cases was 11.86 ±2.33fL and in controls was 11.77 ±1.37fL (P<0.001'S'). The PCT in cases was 0.267 ±0.10 % and in controls was 0.231 ±0.01% (P<0.001 'S')